Hubungan Pengetahuan dengan Perilaku Pencegahan Mahasiswa tentang Covid 19 di Kabupaten Banyuwangi - Annisa Nur Nazmi annisa; Novita Surya Putri (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2022)
Introduction: The transmission of Covid-19 can be prevented with good knowledge and attitudes towards society, one of which is the importance of the role of students. students are demanded as actors in society, because it cannot be denied that students are part of society.Objective: The purpose of this study was determined to describe the correlation between knowledge and student preventive behavior about covid 19 in banyuwangi. Methods: The research used correlational analytic study with cross sectional design. The population of this study were college students in Banyuwangi with the existing sample (targeted sample) and were willing to fill out an online questionnaire via google form as many as 138 respondents . To determine the correlation between knowledge and preventive behavior, the rank spearman correlation test was used. Results: The relationship between student knowledge and behavior to prevent the spread of the COVID-19 virus obtained a p value of 0.000, which means that there is a significant relationship between knowledge and behavior to prevent the spread of the COVID-19 virus. Conclusion: Students are expected to always update their knowledge related to Covid 19, both health students who in the future do practice in hospital services, and non-health students. As well as being able to socialize the importance of PHBS for the prevention of Covid 19 in the community.